2015
DOI: 10.1002/ange.201501443
|View full text |Cite
|
Sign up to set email alerts
|

Radical Compatibility with Nonaqueous Electrolytes and Its Impact on an All‐Organic Redox Flow Battery

Abstract: Nonaqueous redox flowb atteries hold the promise of achieving higher energy density because of the broader voltage window than aqueous systems,b ut their current performance is limited by lowr edox material concentration, cell efficiency,cycling stability,and current density.W er eport an ew nonaqueous all-organic flow battery based on high concentrations of redox materials,w hich shows significant, comprehensive improvement in flow battery performance.A mechanistic electron spin resonance study reveals that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 22 publications
(11 reference statements)
0
38
0
Order By: Relevance
“…[9] Another encouraging research line is the substitution of aqueous electrolytes by non-aqueous electrolytes [10] or even ionic liquids, [11] which are more electrochemically stable and would allow achieving higher battery voltages and energy densities. [12,13] In the last few years, RFBs based on organic redox molecules, such as quinones, phenothiazine, nitroxides, viologens, and pyridines [14][15][16][17] have experienced a great deal of interest, becoming one of the hottest topics in electrochemical energy storage (see Table S1 in the Supporting Information). [18,19] Regardless of the chemical nature of the electroactive species and the type of electrolytes, most RFBs rely on ion-selective membranes to separate the two redox electrolytes and to prevent the crossover of active compounds while allowing the migration of charge carriers.…”
mentioning
confidence: 99%
“…[9] Another encouraging research line is the substitution of aqueous electrolytes by non-aqueous electrolytes [10] or even ionic liquids, [11] which are more electrochemically stable and would allow achieving higher battery voltages and energy densities. [12,13] In the last few years, RFBs based on organic redox molecules, such as quinones, phenothiazine, nitroxides, viologens, and pyridines [14][15][16][17] have experienced a great deal of interest, becoming one of the hottest topics in electrochemical energy storage (see Table S1 in the Supporting Information). [18,19] Regardless of the chemical nature of the electroactive species and the type of electrolytes, most RFBs rely on ion-selective membranes to separate the two redox electrolytes and to prevent the crossover of active compounds while allowing the migration of charge carriers.…”
mentioning
confidence: 99%
“…The combined organic phases were dried over MgSO 4 and then the solvent was removed under reduced pressure to obtain 1 as a colorless solid (5.24 g, 0.045 mol) in a yield of 45%. 1 H NMR (300 MHz, CDCl 3 , δ): 1.24 (brs, 4H, NH 2 ), 1.08 (s, 12H, CH 3 ); 13 Compound 1 (5.2 g, 0.045 mol) was dissolved in tetrahydrofuran (100 ml) and a solution of 2 (8.6 g, 0.021 mol) in tetrahydrofuran (50 ml) was added dropwise. The reaction mixture was stirred at room temperature until the condensation was completed (monitored via thin layer chromatography).…”
Section: Synthesis Of the Nn Containing Compoundmentioning
confidence: 99%
“…[6][7][8][9][10] The development of an all-organic RFB with inexpensive and sustainable redox-active materials and low-cost membranes may overcome these drawbacks. 7,[10][11][12][13][14] Among others, Darling et al 15 conducted cost analyses, which revealed that the price of the active material itself and the membrane represent the main costs of these systems. Cost-efficient organic charge-storage materials can feature a price advantage compared with metal-based RFBs; in particular, if the raw materials are affordable, no synthesis or fewer synthesis procedures are required and the avoidance of elaborate purification steps can be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Benefiting from wider electrochemically stable voltage windows, the emerging nonaqueous RFB (NRFB) holds great potential for overcoming the low energy density challenge present in current state-of-the-art aqueous RFB technologies. [3][4][5][6] Recent research on NRFBs focuses on the development of redox active materials including organometallic compounds, [7][8][9] redox organic materials, [10][11][12] redox active polymers, [13] and the synergy between flow battery and Li-ion or Li-metal battery chemistries. [14][15][16][17][18][19][20] However, the current performance of NRFBs has lagged far behind their inherent capability.…”
Section: Introductionmentioning
confidence: 99%